AUTOMATED SYSTEM FOR BIOMETRIC HEART ANALYSIS: DEVELOPMENT, TECHNICAL ASPECTS, AND PROSPECTS - Яковенко, Ірина; Цомпель, Олександр (SWorldJournal, 2025)
This article presents the development and implementation of an automated system for biometric heart analysis designed as a portable electrocardiograph. The study highlights the device's functional principles, focusing on the processing of bioelectrical s